Dependency on Smartphones: An Analysis of Structural Equation Modelling. - Norazah Mohd Suki; Norbayah Mohd Suki (2013)
This study aims to examine the influence of social needs, social influences and convenience of smartphone on students' dependency on smartphones. A total of 200 completed and usable questionnaires were received from the respondents which comprises of students from one of the public higher education institution in Federal Territory of Labuan, Malaysia by utilizing simple random sampling method where every unit in the population have an equal chance to be selected in the sample. Results via the analysis of structural equation modelling (SEM) show that the relationship between social needs, social influences and convenience of smartphone with dependency on smartphone were supported. The first was found to be the strongest effect. A strong relationship also existed between students' dependency on smartphone and their purchase behavior. Based on the findings, the implications are discussed in the paper and directions for future research are also highlighted.